MILITARY INFORMATION - Gheorghe BOARU; Iulian-Marius IORGA (Annals: Series on Military Sciences, 2016)
The role of information was amplified in the “Information Age” while theories of information have developed continuously. The complexity of this term generated the existence of several definitions and interpretations and a multitude of meanings that are presented in this article in a synthetic manner.Military information became a purpose, a goal, a target, and a means of support for the military actions and sometimes even their result. Moreover, military information is considered “raw material” for “intelligence” that plays the main role within the informational component of military actions aiming at the procurement, processing and transmission of information in order to ensure the effectiveness of energetic component. Informational power, which is the fundamental component of strategic power, depends on the quality and quantity of information in a given time segment and on the ability to efficiently manage and use it in order to make optimal decisions.